RANCANG BANGUN APLIKASI PENJADWALAN MATA PELAJARAN PADA SMA GIKI 2 SURABAYA - Sasongko, Ikhsan Ardi; Nurcahyawati, Vivine; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika, 2020)
In the academic activities of GIKI 2 High School there is a process of scheduling course conducted by the Curriculum Vice Principal to design the course schedule. The scheduling at GIKI 2 High School currently uses conventional way of using Microsoft Excel program to design all schedule of course. In this process appears difficulties in dividing the schedule of courses between teachers because not all days in a week non-permanent teacher can teach and also takes a long time in scheduling process. The length of time required in the process of scheduling this course delay the process of learning activities in GIKI 2 High School. This research aims to produce an scheduling course application at GIKI 2 High School, which can create a one-year course schedule by complying with scheduling constraints such as subjects in the maximum one day of running 2 hours sequentially, maximum teacher teaching hours 8 hours/week and nothing crash between teacher schedule. The system generates a course schedule for one-year course schedule along with the reports required by the school, based on the test results all functions on the system can run well and successfully produce a course schedule along with the necessary reports in the scheduling of subjects.